Recruitment Using Social Networks - D. K. Zakharov (Управление)
The article discusses the broad development of social recruitment - a phenomenon which involves interaction with potential candidates through social networks. Different methods of interaction in social networks with the candidates for the vacant position has been considered. It was found that the function of HR-branding at the company is usually assigned to the Manager of Social Affairs and media. A participation of the HR Manager has been suggested. The importance of creating of special Internet community of the company has been demonstrated and the selection criteria of social networks has been shown. All social networks have their own features. It was concluded that over the time the company which hosts its information and queries in social networks, gaining experience in identifying its target audience, finds preferred candidates and finds out the information for placing in her own Internet community. However, very often, this issue is not addressed at all or meets a sharply negative attitude of the leadership of the company. Leaders still distrust the Internet community in general and social networks in particular, seeing them as an opportunity to «stumble» on random people who are able to harm its activities. The inability to organize the work in social networks deprives the company of a powerful and modern tool to attract qualified personnel.